Equity Yields, Growth, and the Structure of Share Prices - Malkiel, Burton G. (American Economic Review, 1963)
The first half of 1962 witnessed one of the most precipitous decliues in stock market prices in recent history. In terms of the volume of trading and the magnitude of the daily erosion of stock values, one must look back to the crashed of 1929 and 1937 to find parallels. Moreover, the decline was not confined to U. S. stock prices, for a world-wide revaluation of equity values was transmitted from New York. For most professional financial observers of these developments, two aspects of the decline served as the foci of their analysis. There was first the sharp drop in the level of share prices. Second, and perhaps more interesting, there was a marked change in the structure of share prices, i.e. the relationships among equities of different characteristics.